Artificial Intelligence in Higher Education: Perspicacity Relation between Educators and Students - Muhammad Mushfi El Iq Bali; Maharani Putri Kumalasani; Devi Yunilasari (Journal of Innovation in Educational and Cultural Research, 2022)
Artificial intelligence is a system with the nature of human intelligence that can automatically provide knowledge and information to create intelligent applications to make it easier to solve problems such as problem-solving, speech recognition, and learning. This research was investigated to find out and understand the relationship of intelligence between educators and students in applying artificial intelligence in universities. The method used is a phenomenological type of qualitative method. This research was conducted at Nurul Jadid University (UNUJA), with the subject of research being PAI lecturers and students in semester V. This research phase was carried out by preliminary studies, observation, data collection (interviews), data verification, and drawing conclusions. As for the results of this study, in its application, artificial intelligence in universities has a positive and negative impact on the relationship of intelligence to learning when it is carried out outside conventional learning. The intelligence relationship between educators and students, which includes Intelligence Quotient (IQ), Emotional Quotient (EQ), and Spiritual Quotient (SQ) contained in it, is also a positive thing that coexists and is directed.